2009
DOI: 10.1167/iovs.08-3146
|View full text |Cite
|
Sign up to set email alerts
|

Resolvins E1 and D1 in Choroid-Retinal Endothelial Cells and Leukocytes: Biosynthesis and Mechanisms of Anti-inflammatory Actions

Abstract: The interplay of inflammatory stimuli-activated CRECs and leukocytes biosynthesizes RvE1 and RvD1 from EPA and DHA. These resolvins inhibit inflammatory signaling from CRECs and leukocytes and inflammatory activity as PMN transmigration across CRECs barriers. Thus, these resolvins and their biosynthesis pathways are potential targets for novel treatment of inflammatory ocular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 45 publications
2
60
0
Order By: Relevance
“…However, VCAM-1 immunoneutralization has shown higher therapeutic effects than that of ICAM-1 in experimental colitis (49). Furthermore, our findings are in line with previous studies that have shown that RvE1 and RvD1 reduce PMN transmigration across choroid retinal endothelial cells stimulated with IL-1b and that this effect is dependent on VCAM-1 expression (50). In addition, in vitro incubation with EPA or DHA has been shown to decrease VCAM-1, ICAM-1, and LFA-1 expression in human epithelial cells stimulated with LPS (51).…”
Section: Discussionsupporting
confidence: 92%
“…However, VCAM-1 immunoneutralization has shown higher therapeutic effects than that of ICAM-1 in experimental colitis (49). Furthermore, our findings are in line with previous studies that have shown that RvE1 and RvD1 reduce PMN transmigration across choroid retinal endothelial cells stimulated with IL-1b and that this effect is dependent on VCAM-1 expression (50). In addition, in vitro incubation with EPA or DHA has been shown to decrease VCAM-1, ICAM-1, and LFA-1 expression in human epithelial cells stimulated with LPS (51).…”
Section: Discussionsupporting
confidence: 92%
“…macrophages in vitro. Decrease in IL-8, a potent PMN chemoattractant, has also been shown for other SPMs, including RvD1, 25 and is consistent with the decrease in PMN levels during bacterial infection (Figures 2 and 6). The reduction in tumor necrosis factor-a and IL-6 (pyrogenic cytokines) is an action also shared with RvD1, RvD2, and RvD3.…”
Section: Discussionsupporting
confidence: 84%
“…20,21 Briefly, peripheral blood samples were mixed with the same volume of PBS containing 4% dextran and were centrifuged at 150 ϫ g for 15 minutes. Platelet-rich supernatant was further centrifuged at 1600 ϫ g for 15 minutes to collect platelets.…”
Section: Cell Culturesmentioning
confidence: 99%
“…They also likely enhance 12/15-lipoxygenase-like activity, 26 which results in 14-hydroxylation of DHA and some DHA derivatives. 20 Each incubation was extracted for analysis and preparative separation of 14S,21R-diHDHA or its biosynthetic intermediates. The pH of each incubation was adjusted to pH 4.5 with HCl (1 mol/L, on ice) and then the incubation was mixed with three volumes of ice-cold methanol (sample:methanol ϭ 1:3 v/v).…”
Section: Cell Culturesmentioning
confidence: 99%